2020
DOI: 10.1088/1361-665x/ab7842
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial cellulose coated ST-cut quartz surface acoustic wave humidity sensor with high sensitivity, fast response and recovery

Abstract: A Love mode surface acoustic wave (SAW) humidity sensor based on bacterial cellulose (BC) coated ST-cut quartz was developed in this study. The BC film is composed of ultrafine interwoven fibers to form a highly porous network, and its surface contains a large amount of hydroxyl groups, which significantly improve the adsorption capability of SAW sensing layer for water molecules. This results in significant mass loading effects and enhanced responsivity of the SAW sensor. The resonant frequency of the sensor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 38 publications
0
18
0
Order By: Relevance
“…Thus, not only a novel highly stable humidity sensor was explored, but also a new application for BC was opened. A surface acoustic wave humidity sensor with improved sensitivity and selectivity was developed, Wang et al [69] first reported such a BC-based sensor, which exhibited enhanced sensitivity, fast response, and superior repeatability for humidity sensing. In addition, different BC sensing materials to detect steam also have been reported [70] (Figure 6d).…”
Section: Humidity Sensingmentioning
confidence: 99%
“…Thus, not only a novel highly stable humidity sensor was explored, but also a new application for BC was opened. A surface acoustic wave humidity sensor with improved sensitivity and selectivity was developed, Wang et al [69] first reported such a BC-based sensor, which exhibited enhanced sensitivity, fast response, and superior repeatability for humidity sensing. In addition, different BC sensing materials to detect steam also have been reported [70] (Figure 6d).…”
Section: Humidity Sensingmentioning
confidence: 99%
“…1(d)] and recently, researchers have utilised this configuration to develop gas and humidity sensors. [11][12][13] For example, Pasupuleti et al 11 fabricated a langasite-based SAW resonator sensor with a GO-PEDOT:PSS nanocomposite coated in the region between the IDTs of the resonator for nitrogen dioxide sensing. 11) After coating, the insertion loss increased slightly but the response was not altered significantly and the quality factor decreased slightly.…”
Section: Introductionmentioning
confidence: 99%
“…The sensor was made on a ST-cut quartz substrate which has a low temperature coefficient of frequency (TCF). However, the performance was poorly affected with changes in humidity, because the amine groups of PEI and the hydroxyl groups of BC have strong adsorptions of H2O molecules [20,21], thus causing significant mass loading.…”
Section: Introductionmentioning
confidence: 99%